2019
DOI: 10.7759/cureus.4375
|View full text |Cite
|
Sign up to set email alerts
|

Ethylene Glycol Toxicity in the Setting of Recurrent Ingestion: A Case Report and Literature Review

Abstract: Ethylene glycol (EG) poisoning is a toxicologic emergency requiring high clinical suspicion and early diagnosis to prevent life-threatening complications. Direct EG quantification methods involve cumbersome and time-consuming laboratory tests of limited utility in the emergency setting. Accordingly, the osmolal gap is frequently employed as a surrogate screening method in cases of suspected toxic alcohol poisoning. However, the osmolal gap has several inherent limitations to be considered when used as a diagno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Although not as commonly ingested as ethanol, ingestion of other toxic alcohols remains a significant public health problem [[1], [2], [3], [4], [5], [6]]. The toxic alcohols include methanol, isopropanol, and ethylene glycol.…”
Section: Introductionmentioning
confidence: 99%
“…Although not as commonly ingested as ethanol, ingestion of other toxic alcohols remains a significant public health problem [[1], [2], [3], [4], [5], [6]]. The toxic alcohols include methanol, isopropanol, and ethylene glycol.…”
Section: Introductionmentioning
confidence: 99%
“…Thomas and Leung reported that the hybrid solar cell made on a planar Si substrate using the mixed cosolvent of EG and methanol (MeOH)-engineered PEDOT:PSS film shows a high efficiency exceeding 14.6% . Due to the high dielectric constant and high boiling point of PEDOT:PSS, the insulating PSS can be removed by weakening the interaction between PEDOT and PSS. However, ethylene glycol (EG) and dimethyl sulfoxide (DMSO) , have certain negative effects on human beings and the environment.…”
Section: Introductionmentioning
confidence: 99%